Influence of environment on thermal ecology of direct-developing frogs (Anura: craugastoridae: pristimantis) in the eastern Andes of Colombia (2019)
Amphibian's temperature is a critical variable in the biology and ecology of organisms, especially ectotherms whose body temperatures depend on environmental conditions. In this study we compared the thermal biology of 13 species of frogs of the genus Pristimantis across 11 sites across different elevations in the Eastern Andes of Colombia, and sought to correlate ecophysiological variation with environmental variation at two scales. We measured critical thermal maximum (CTMax) and critical thermal minimum (CTMin) temperatures of reach frog, along with air temperature, and microhabitat temperature and structure. As the height of the locality increases, CTMin decreases in greater scale in relation to the CTMax, which is high in relation to the maximum temperature reported for highlands. There are also differences in thermal physiology between the flanks of the mountain range. The variables of herbaceous cover, litter cover and Humidity are related to the thermal limits of the species. The changes in thermal physiology include a dynamic that involves not only altitudinal and latitudinal changes, but also the structure and composition of the microhabitats that each species inhabits, as well as the evolutionary history of the species, which can contribute to the conservation of characters such as the CTMax in highland species, which, in turn, raises new questions regarding the survival of species in the face of climate change phenomena.